2020
DOI: 10.1007/s11423-020-09863-5
|View full text |Cite
|
Sign up to set email alerts
|

Designing teacher professional development programs to support a rapid shift to digital

Abstract: From a design perspective, this paper offers a response to the impact, value, and application of a manuscript published by Philipsen et al. (Improving teacher professional development for online and blended learning: A systematic meta-aggregative review. Educational Technology and Research Development, 67, 1145–1174. 10.1007/s11423-019-09645-8, 2019). Philipsen et al. (2019) reviewed what constitutes an effective teacher professional development program (TPD) for online and blended learning (OBL), with our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…They also regarded the OTPDP as a flexible, inexpensive, and easy-to-access program with lecture videos that they could attend anywhere and anytime. Heap et al, (2020) also state that OTPDPs should be flexible, accessible, and affordable. The results are consistent with the literature (Martin, 2012;Persons et al, 2019;Robinson, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also regarded the OTPDP as a flexible, inexpensive, and easy-to-access program with lecture videos that they could attend anywhere and anytime. Heap et al, (2020) also state that OTPDPs should be flexible, accessible, and affordable. The results are consistent with the literature (Martin, 2012;Persons et al, 2019;Robinson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They came up with solutions to problems regarding training, content, environment, and conditions. Although Internet access and infrastructure are critical for effective OTPDPs (Heap et al, 2020;Polly & Martin, 2020), online learning is imbued with connection or technical issues (Hodges et al, 2016;Sukhbaatar et al, 2018;Yıldırım, 2020a;Zhao, 2003). The fourth part of the first research question looked into what teachers thought about group work within the scope of the OTPDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of eleven academics over six years from Finland revealed that TPD that sought to build reflective practice and peer interaction assisted most in the development of a teacher identity (Nevgi & Lofstrom 2015). Although developed pre-pandemic, responses to the six component TPD framework suggested by Philipsen et al (2019), agree that whilst it provides a useful mechanism to structure a post-COVID TPD discussion (Heap, Thompson & Fein 2020;Lockee 2020;Portillo & Lopez de la Serna 2020) the fact that it was conducted in a West-European context 'is an overall limitation from an international perspective' (Portillo & Lopez de la Serna 2020: 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whilst much of the focus has been about 'pivoting online' in order to cope with the immediate emergency, this only captures part of the challenge. In the UK at least, surveys show an increasing percentage of lecturers and executive leaders in HEI believe online will be a fundamental component of the future (JISC 2020;McVitty 2021) and preparation is urgent (Heap, Thompson & Fein 2020;Glantz & Gamrat 2020). Developing systems and resources -via TPD, for example -'…that can be leveraged in times of shock when core delivery models are disrupted' is vital for future sustainability (Portillo & Lopez de la Serna 2020: 3).…”
Section: Introductionmentioning
confidence: 99%